Analysis of the Influence of Gross Regional Domestic Product (GRDP), Minimum Wage, Population, Education, and Unemployment on Labor Force Absorption in Districts/Cities of Central Java Province, 2017-2021: Analisis Pengaruh PDRB, Upah Minimum, Jumlah Penduduk, Pendidikan Dan Pengangguran Terhadap Penyerapan Tenaga Kerja Di Kabupaten/Kota Provinsi Jawa Tengah Tahun 2017-2021 - Nabila Ayu Atikasari; Rifki Khoirudin; Rahmat Saleh (Institute of Educational, Research, and Community Service, 2023)
Labor is an object of development which has a very important aim in increasing production output. The employment problem currently being faced is the rapid increase in the number of workers which cannot be balanced with the available job opportunities. This research aims to analyze the influence of Gross Regional Domestic Product, Regency/City Minimum Wage, Population, Education and Unemployment on labor absorotion in Central Java in 2017-2021. This data was obtained from the Central Java Statistics Agency. Quantitative Analysis is this research uses the Fixed Effect Model. The estimation result is this study show that Gross Regional Domestic Product has a positive ans not significant effect, Regency Minimum Wage has a negative relationship and has no significant effect, Education has a positive relationship and has no significant effect, Population has a negative and not significant effect and Unemployment has negative relationship and has a significant effect on labor absorption in Central Java in 2017-2021. Together, all variables have an influence on labor absorption in Central Java